Dorsolateral Onlay OMG Urethroplasty through Unilateral Urethral Mobilization in Anterior Urethral Stricture - Our Experience in Dhaka Medical College Hospital and Salam Urology & Transplantation Foundation of Bangladesh (SUTF) (Bangladesh Journal of Urology, 2012)
Introduction: Circumferential urethral mobilization may result in ischemia of urethra in conventional anterior dorsal onlay urethroplasty. We performed dorsolateral onlay OMG urethroplasty in anterior urethral stricture through unilateral mobilization of urethra to preserve its vascular supply. Objective: To evaluate the feasibility and short term outcome of using dorsolateral onlay OMG urethroplasty in anterior urethral stricture through unilateral urethral mobilization. Method: In this prospective study, 27 patients with average age of 38 years underwent anterior dorsolateral onlay OMG urethroplasty through unilateral urethral mobilization in tertiary care hospital. In all patients, the surgical approach to the anterior urethra was made only along one side leaving the urethra attached to the corpora cavernosa on the opposite side thus preserving its vascular supply intact on one side. The cause of stricture was instrumentation in four cases (14%), lichen sclerosis in thirteen cases (48%), unknown in seven cases (25%) and infection in three cases (11%).The stricture site was bulbar in 10 cases and panurethral in 17 cases. Average length of the stricture segment was 4cm and 9 cm in bulbar and panurethral respectively. Of 27 patients, 20 received previous treatment. Clinical outcome was considered a failure when postoperative Qmax was